Effects of cellulase and Lactiplantibacillus plantarum on silage performance, microbial community composition and volatiles of Caragana korshinskii - Peiqing Zhang; Baochao Bai; Tianrong Zhou; Wei Wang; Lianyun Zhang; Xiaojun Wei; Hongbo Li; Zhijun Wang (BMC Microbiology)
Abstract Caragana korshinskii as a geogenic non-conventional forage is underutilized due to high lignocellulose and the presence of specific odors. The aim of this study was to investigate the effects of no additives (CK), cellulase (CE) and Lactiplantibacillus plantarum (LAB) on Caragana korshinskii silage quality, microbial community structure and volatiles. The results showed that both cellulase and Lactiplantibacillus plantarum were able to enhance fermentation quality by lowering the pH value and increasing the lactic acid (LA) content of Caragana korshinskii silage. In addition, cellulase was more effective in decreasing neutral detergent fiber (NDF) content and acid detergent fiber (ADF) content, and increasing water-soluble carbohydrate (WSC) content (p<0.05). Microbial community analysis showed that the addition of cellulase significantly reduced the microbial diversity of Caragana korshinskii silage and simplified the flora structure (p<0.05), with the relative abundance of the dominant bacterium Limosilactobacillus accounting for 82.78%, while suppressing undesirable microorganisms such as Klebsiella and Enterobacter. Analysis of volatile compounds showed that terpenes (54.35%) and alcohols (27.49%) were the main volatile organic compounds in fresh samples of Caragana korshinskii, and the addition of LAB was able to reduce the content of terpene volatiles. Furthermore, silage treatment was able to improve the palatability of Caragana korshinskii by eliminating irritating odors such as 2-Methylnaphthalene and Naphthalene. These results suggest that silage can improve the odor of Caragana korshinskii and that cellulase is more beneficial as a silage additive to improve silage quality.